2006
DOI: 10.1007/s11249-006-9028-5
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquids as lubricants of polystyrene and polyamide 6-steel contacts. Preparation and properties of new polymer-ionic liquid dispersions

Abstract: Room-temperature ionic liquids (ILs) have been used as external lubricants in polystyrene (PS) and polyamide 6 (PA6)-steel contacts and as internal lubricants in new polymer-IL dispersions. 1)C n H 2n+1 )3)CH 3 -imidazolium X ) [X=BF 4 ; n=2 (IL1), 6 (IL2), 8 (IL3). X=PF 6 ; n=6 (IL4). X=CF 3 SO 3 ; n=2 (IL5). X=(4)CH 3 C 6 H 4 SO 3 ); n=2 (IL6)] ionic liquids give low friction and extremely mild wear in PS/AISI 316L stainless steel contacts, independently of IL composition. For AISI 52100 steel pins a triboco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
77
0
10

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(88 citation statements)
references
References 28 publications
1
77
0
10
Order By: Relevance
“…This further stresses the relevance of the encapsulation concept for controlled, on-demand release at the contact surface. However, the works by Sanes et al [15] and Saur´ın et al…”
Section: Introductionmentioning
confidence: 97%
“…This further stresses the relevance of the encapsulation concept for controlled, on-demand release at the contact surface. However, the works by Sanes et al [15] and Saur´ın et al…”
Section: Introductionmentioning
confidence: 97%
“…In recent studies, we have shown that it is possible to improve the tribological performance of thermoplastics [34][35][36][37][38][39] and of epoxy resin [40] against steel by preparing new dispersions containing variable concentrations of ILs or IL-modified ZnO nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10][11][12] ILs generally show outstanding thermo-oxidative stability, this property being particularly important for lubricants that are used under extreme conditions. …”
mentioning
confidence: 99%